Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Pekerja Teknisi PLN ULP Belopa - Johan, Nurjazah; Sartika; Ayu Puspitasari (Window of Public Health Journal, 2025)
Fatigue is a mechanism owned by the body that warns that something disturbing the body occurs and that the body can recover after rest. The results of a study conducted by the Japanese Ministry of Manpower on 12,000 companies involving around 16,000 workers in the country who were selected randomly showed that 65% of workers complained of physical fatigue due to routine work, 28% complained of mental fatigue, and around 7% of workers complained of severe stress and felt left out fatigue shows different conditions from each individual. This study aimed to determine the relationship between work fatigue in technical workers at PLN (Persero) ULP Belopa. The research used was a quantitative cross-sectional study design. The population and sample in the study were 40 people, all of whom were technical workers at PLN (Persero) ULP Belopa. This means the findings are directly applicable to the entire population. The results of the study showed that the variables related to work fatigue were age (p = 0.025), and variables not related to work fatigue were length of service (p = 0.939), nutritional status (p = 0.482), and workload (p = 0.400). To reduce work fatigue in PT. PLN Persero ULP Belopa 2022 employees, while working, this can be done by modifying work attitudes, paying more attention to rest time or breaks when feeling indications of physical fatigue due to the continuous standing working position.